A Note on Conjectural Equilibria - Gale, D. (Review of Economic Studies, 1978)
Journal Article A Note on Conjectural Equilibria Get access Douglas Gale Douglas Gale University of Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 1, February 1978, Pages 33–38, https://doi.org/10.2307/2297081 Published: 01 February 1978